Pengaruh COVID-19 Terhadap Operasional Dining Room Restoran Penyedia Hidangan Barat di Ruko Golden 8, Gading Serpong, Kecamatan Kelapa Dua, Tangerang - Carmelia, Riesta; Carvina, Aurelie; Agustiana, Sindi; Lemy, Diena Mutiara (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2021)
This study aims to find out the impacts, efforts, and constraints of restaurant managers in dealing with the Covid-19 pandemic and the new normal. The research method used is qualitative research with exploratory descriptive analysis. The population and samples used in this study were three people who manage the restaurant at Ruko Golden 8 Gading Serpong, Kelapa Dua District, Tangerang, each restaurant representing one person to be interviewed. The results of this study revealed that the Covid-19 pandemic and the new normal have a big impact on the sustainability of restaurant.